SYMMETRIC BANACH-KANTOROVICH SPACES (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2025)
Let $B$ be a complete Boolean algebra, let $Q(B)$ be the Stone compact of $B$, let $C_\infty (Q(B))$ be the commutative unital algebra of all continuous functions $x:Q(B) \rightarrow [-\infty,+\infty],$ assuming possibly the values $\pm\infty$ on nowhere-dense subsets of $Q(B)$. We consider Maharam measure $m$ defined on $B$, which takes on value in the algebra $L^0$ of all real measurable functions. With the help of the property of equimeasurablity of elements from $ C_\infty (Q(B))$, associated with such a measure $m$, the notion of a symmetric Banach-Kantorovich space $(E,\|\cdot|_{E})$ over $L^0$ is introduced and studied in detail. Here $E\subset C_\infty (Q(B)),$ and \ $\|\cdot|_{E}$ -- $L^0$-valued norm in $E$, endowing it with the structure of the space Banach-Kantorovich. Examples of symmetric Banach-Kantorovich spaces are given, which are vector-valued analogues of classical $L^p$-spaces, $ 1\leq p \leq \infty$, associated with a numerical $\sigma$-finite measure.